Ferrimicrobium acidiphilum Exchanges Electrons With a Platinum Electrode via a Cytochrome With Reduced Absorbance Maxima at 448 and 605 nm - Blake, Robert C.; Nautiyal, Amit; Smith, Kayla A.; Walton, Noelle N.; Pendleton, Brealand; Wang, Zhe (Frontiers in Microbiology, 2021)
Ferrimicrobium acidiphilum is a Gram-positive member of the Actinobacteria phylum that can respire aerobically or anaerobically with soluble Fe(II) or Fe(III), respectively, in sulfuric acid at pH 1.5. Cyclic voltammetry measurements using intact Fm. acidiphilum at pH 1.5 produced fully reversible voltammograms that were highly reproducible. The maximum current observed with the anodic peak was considerably less than was the maximum current observed with the cathodic peak. This difference was attributed to the competition between the platinum electrode and the soluble oxygen for the available electrons that were introduced by the cathodic wave into this facultative aerobic organism. The standard reduction potential of the intact organism was determined to be 786 mV versus the standard hydrogen electrode, slightly more positive than that of 735 mV that was determined for soluble iron at pH 1.5 using the same apparatus. Chronocoulometry measurements conducted at different cell densities revealed that the intact organism remained in close proximity to the working electrode during the measurement, whereas soluble ionic iron did not. When the cyclic voltammetry of intact Fm. acidiphilum was monitored using an integrating cavity absorption meter, the only small changes in absorbance that were detected were consistent with the participation of a cellular cytochrome with reduced absorbance peaks at 448 and 605 nm. The cytochrome that participated in the exchange of electrons between the intact organism and extracellular solid electrodes like platinum was the same cytochrome whose oxidation was previously shown to be rate-limiting when the organism respired aerobically on extracellular soluble iron.